PERANAN EXECUTIVE CHEF DALAM FOOD & BEVERAGE PRODUCTION DEPARTEMENT UNTUK MENANGANI BANQUET EVENT DI HOTEL FORMOSA MANADO - Sony Wijanarko; Agus Walansendow (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2023)
The working relationship between the Food & Beverage Product or Kitchen and the Banquet Service in general is that the kitchen section handles the food processing process while the Banquet Service section handles the food service process (service), if the two parts work together well then the goals that have been set together will go well, in this case, the goal is to organize a Banquet Event. In this study, the authors conducted research on Hotel Formosa Manado, which is a two-star hotel (**) in the category of business hotel located in the shopping complex of the Bahu Mall Boulevard. By focusing only on one variable that is measured, namely the Role of the Executive Chef in the Banquet Event at the Formosa Manado Hotel. The data obtained were analyzed descriptively qualitatively, that is, describing and explaining the circumstances under study systematically on how the role of the Executive Chef in the Banquet Event at Hotel Formosa Manado for 5 months. Based on the description of the results of the analysis in writing this skripsi, the writer can conclude that in the process of handling banquet events, a solid work team is needed, starting from the first time the customer meets with sales marketing, in this case, the banquet coordinator until function sheets are made and distributed to the department responsible for implementing the banquet event.